Delineating the Immuno-Dominant Antigenic Vaccine Peptides Against gacS-Sensor Kinase in Acinetobacter baumannii: An in silico Investigational Approach - Smiline Girija, A. S. (Frontiers in Microbiology, 2020)
Abstract: Objectives: To predict the novel vaccine peptide candidates against gacS protein involved with the citrate utilization in the two component system of A.baumannii associated virulence as an alternative strategy to combat the multi-drug resistant strains using immuno-informatic approach. Methods: The study is designed as an observational in-silico study design with the application of BepiPred, AlgPred, Vaxijen, AntigenPro, SolPro, Expasy Protparam server, IEDB database and MHC cluster analytical tools and servers to predict the immuno-dominant B-cell and T-cell epitopes from gacS FASTA sequences retrieved from UNIPROT database. Further peptide interactions with TLR-4 was assessed based on the number of hydrogen bonds. Results: 9 peptides (20aa) with the highest score of 1 were selected from the 137 epitopes and 5 were predicted as antigenic epitopes (E1 to E5). E3 was selected as the potent antigen (score: 0.939537) and E1 as the best vaccine candidate (score: 0.9803) under AntigenPro and Vaxijen server respectively. SolPro predicted all epitopes as soluble peptides. ProtParam predictions showed E3 and E5 as stable proteins with a shelf life of 3.5 hrs and 1.9 hrs and possessed negative GRAVY values. PsortB server predicted a final localization score of 7.88 for the gacS protein sequence as a cytoplasmic membrane protein. IEDB conservancy analysis showed 100% conserved sequences within the gacS sequence and class I conservancy yielded positive values for all epitopes. Cluster analysis showed strong interactions and the protein-peptide interactions with TLR-2 finally detected E5 as the best interacting peptide (H bonds=14) followed by E3 (H bonds=12). Conclusion: The study suggests 5 antigenic peptides as promiscuous vaccine candidates to target the gacS of A.baumannii using immuno-informatic approach towards the peptide synthesis and in-vitro analysis. However the study recommends further experimental validation for immunological response and memory through in-vivo studies.